Analisa Karakteristik Perusahaan, Opini Audit, Struktur Modal, Struktur Kepemilikan Terhadap Kinerja Perusahaan dengan Good Corporate Governance sebagai Variabel Moderasi pada Perusahaan Tekstil dan Garmen - Nur Fitroten Dian Sari; Hwihanus Hwihanus (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study aims to analyze the effect of company characteristics, audit opinion, capital structure, and ownership structure on company performance with Good Corporate Governance (GCG) as a moderating variable in the textile and garment industry listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022. The results showed that company characteristics have a significant effect on audit opinion, ownership structure, and capital structure, but have no effect on company performance. Audit opinion, capital structure, and ownership structure also have no significant effect on company performance. In addition, GCG cannot moderate the relationship between these variables and company performance. This study emphasizes the importance of internal corporate management and evaluation of GCG implementation to improve the competitiveness of companies in facing global challenges.